Between the Manuscript and the Book: Functions of the Editor - Girčienė, Jurgita (Knygotyra, 2020)
This article, based on interviews with representatives of Lithuanian publishing houses, describes the editor’s role in contemporary publishing. It is showed that editors contribute to strategic and managerial processes within the publishing houses and are responsible for the process of editing manuscripts. Even though certain publishing houses retain the habit of referring to the senior or chief editor as the one engaged in strategic activity, today many of the houses have project manager positions tasked with shaping the publishing portfolio. Today’s editors engage in managerial activities rarely; their main field of responsibility remains editing manuscripts. The clearest functions are associated with microlevel text specialization: copyeditors, proofreaders, and editors handling book layouts. Lithuanian publishing houses are yet to develop a clearly defined role of content editors, which is customary in other countries wherein the publishing industry had developed more consistently. According to the publishers, Lithuanian publishing houses face a lack of experts able to refine the contents of the manuscripts, i.e., to offer macrolevel text editing services.
Keywords: editor; content editor; copyeditor; levels of editing; editorial publishing processes